The Altered Shall Inherit the Earth: Biopower and the Disabled Body in Texhnolyze. - Boyd, Nolan (Science Fiction Studies, 2018)
The anime series Texhnolyze (2003) is set in the underground city of Lux, where the human body’s ability to heal and repair itself has degraded. Those who wield power and can afford it have their amputated limbs replaced with advanced robotic prosthetics in a process known as texhnolyzation. The disabled body is many things in this world: a marker of class, a political cause, the locus of religious zealotry, and the symbol of humanity’s decline. The disabled body within this text is deeply enmeshed in biopolitical systems that organize power. By examining the flow of power throughout the series among the three leading groups in the city, the medical and scientific discourse surrounding texhnolyzation, and the violent actions of the Class, the city’s elite, I trace the operation of different forms of biopower and examine the series’ relation to the disabled body and to the prosthetic technology of texhnolyzation. I argue that Texhnolyze resists ableist cultural and medical narratives as I examine how it engages with problematic representations of posthuman ideologies.